Comparative study of microwave absorption properties of Ni–Zn ferrites obtained from different synthesis technologies. Issue 16 (15th August 2022) - Song, Jiali; Gao, Yu; Tan, Guoguo; Man, Qikui; Wang, Zhi
Abstract: Spinel ferrites are widely used for electromagnetic wave (EMW) absorption applications. In this study, spinel Ni–Zn ferrites with excellent microwave absorption properties were synthesized. Their EMW absorption characteristics and interaction mechanisms were studied to lay the foundation for the study of the role of Ni–Zn ferrite as a magnetic substrate for composites. Herein, Ni0 · 5 Zn0 · 5 Fe2 O4 was prepared by the hydrothermal method (H-NZFO) and the sol–gel auto-combustion method (S-NZFO); both samples exhibited distinct microwave absorption properties. The S-NZFO absorber (thickness = 3.72 mm) demonstrated the best dual-zone microwave absorption with two strong reflection loss peaks at 5.1 and 10.5 GHz. The corresponding effective absorption bandwidth (EAB) reached 9.0 GHz, which covered part of the S-band and all of the C- and X-bands. These results were attributed to the high saturation magnetization, outstanding complex permeability, and multiple magnetic loss channels of S-NZFO. The H-NZFO sample exhibited excellent absorption capability and matching thickness. At a thickness as low as 1.71 mm, the minimum reflection loss ( RL min ) of the H-NZFO absorber reached -60.2 dB at 13.1 GHz. The maximum bandwidth corresponding to RL below -10 dB was 4.6 GHz. These results can be attributed to small particle size, high complex permittivity, and multiple dielectric loss channels of H-NZFO. The observed wide effective absorption bandwidth of S-NZFO and strong microwave absorption capability of H-NZFO suggest the potential of both materials as substrates for efficient microwave absorbers in military as well as civilian absorption applications.